Goal-Directed Achievement Through Geographic Location (GAGL) Reduces Patient Length of Stay and Adverse Events. (July 2020) - Maniaci, Michael J.; Dawson, Nancy L.; Cowart, Jennifer B.; Richie, Eugene M.; Suryaprasad, Anil G.; Hodge, David O.; Joyce, Nicole E.; Kernan, Carol A.; Stone, Laurie A.; Burton, M. Caroline
This prospective cohort study aimed to improve hospital outcomes through geographic location of hospitalist patients and conducting daily multidisciplinary team rounds—Goal-directed Achievements through Geographic Location (GAGL). Patients were admitted to a geographic (GAGL) study unit where daily multidisciplinary rounds took place among nursing, case management, a hospitalist, pharmacy, physical and occupational therapy, respiratory therapy, and nutrition services. A total of 985 (56.4%) patients were admitted to the GAGL study unit and 760 patients (43.6%) were admitted to non-GAGL units. Patients admitted to the GAGL study unit had a shorter average length of stay (3.64 days vs 4.35 days, P = .0001) and a lower number of risk events (91 [9.2%] vs 93 [12.2%], P = .038). There was no significant difference in 30-day readmissions, avoidable day events, or code blue team activations. GAGL provides a framework for hospital organizations to improve provider communication, hospital efficiency, and patient safety.